Assessment on Accuracy of Design Science Research (DSR) Frameworkas a Daylighting MeasurementTool for Islamic Religious School - Raja Nur Syaheeza, Raja Mohd Yazit; Elina, Mohd Husini; Mohd Khedzir, Khamis; Yakubu Aminu, Dodo (2021)
Daylight efficiency correlates towindow design. Standards and guidelines recommended 20% window to floor ratio (WFR) at 800mm to 900mm windowsill height for classrooms, where it should provide the recommended illuminance level between 300 lx to 500 lx measured at workingplane height (WPH) between 800mm to 900mm. Instead, Islamic religious schools use ‘rehal’ at 300mm WPH. Since that the WPH is lower, the measured illuminance level is at different intensity. This paper assesses the accuracy of Design Science Research (DSR) methodology framework adaptation in measuring and designing daylight consideration in Islamic religious schools that uses lower working plane height.